Kawasan Objek Wisata Danau Molara Di Kabupaten Konawe Utara - Krisdianto, Krisdianto; Nahdatunnisa, Nahdatunnisa; Ahyarki Abidin, Afri (Architectura : Journal of Architecture and Planning, 2025)
Molara Lake in North Konawe Regency is one of the natural tourism potentials that has not been optimally explored. The development of this area as a tourist destination can have positive impacts on the local economy and environmental conservation. This study aims to design the Molara Lake tourism area using an ecological architecture approach, emphasizing the harmonious integration between architectural design and the natural environment to create a sustainable and eco-friendly tourism area. The research methodology applied is descriptive qualitative, which includes data collection techniques through field observations, in- depth interviews with relevant stakeholders, and comprehensive literature studies. The results of the study show that Molara Lake has great potential as a premier tourist destination, but this potential has not been optimally utilized. The application of the ecological architecture approach is expected to enhance the tourism appeal of Molara Lake while maintaining ecosystem balance and environmental sustainability. This research provides significant contributions to the development of sustainable tourism that can be applied to other areas with similar natural potentials.